2018
DOI: 10.1111/phen.12274
|View full text |Cite
|
Sign up to set email alerts
|

Roles of the circadian clock and endocrine regulator in the photoperiodic response of the brown‐winged green bug Plautia stali

Abstract: The physiological mechanisms underlying photoperiodism in insects have been studied extensively, although the associated molecular machinery remains largely unknown. In the present study, we investigate the roles of the circadian clock gene cycle (cyc) and the endocrine regulator gene myoinhibitory peptide (Mip) in the photoperiodic response of the brown‐winged green bug Plautia stali Scott (Hemiptera, Pentatomidae). Typically, adult females of this species develop their ovaries under long‐day conditions, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(6 citation statements)
references
References 76 publications
(107 reference statements)
0
5
0
Order By: Relevance
“…Primer sets for amplifying the cDNA containing the T7 promoter are shown in SI Appendix, Table S3. The primers for bla and per were created by referring to previous studies (11,60). The concentration of dsRNA was adjusted to 1 μg/μL, with pure water as the working solution.…”
Section: Methodsmentioning
confidence: 99%
“…Primer sets for amplifying the cDNA containing the T7 promoter are shown in SI Appendix, Table S3. The primers for bla and per were created by referring to previous studies (11,60). The concentration of dsRNA was adjusted to 1 μg/μL, with pure water as the working solution.…”
Section: Methodsmentioning
confidence: 99%
“…Advanced genetic analyses using insect models have suggested that circadian clock genes are involved in photoperiodism [8][9][10][11][12][13]33,[40][41][42]. However, neural signaling pathways that convey the photoperiodic information based on clock genes remain largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In 1936, Bu ¨nning proposed a model in which endogenous circadian rhythms underlie the time measurement of photoperiod [1], and subsequent studies have examined the relationship between the circadian clock system and photoperiodic responses in both vertebrates and invertebrates [2][3][4][5][6][7]. Previous studies using insect models demonstrated that genetic suppression of expression of clock genes disrupted not only circadian rhythms but also photoperiodic responses of reproduction [8][9][10][11][12][13][14]. Thus, the molecular basis of the circadian clock is essential for photoperiodic responses.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it was proven that in Drosophila sNPF acts synergistically with PDF to inhibit reproductive arrest via activation of insulins producing cells in the brain (Nagy et al, 2019). Additionally, other neuropeptides, like diuretic hormone 44 (DH44) (Hasebe and Shiga, 2021) or Myoinhibitory peptides (MIPs) (Tamai et al, 2019) whose release is under circadian clock control, were shown to also participate in the regulation of imaginal diapause. Taken together, our data show that the photoperiodic regulation of the P. apterus diapause is regulated by CRY-m via the regulation of the PDF level in the Dp and others, currently unknown factors.…”
Section: Connection Of the Cry-m And Pdf To The Photoperiodic Regulat...mentioning
confidence: 99%